Quantification of the Lewis Basicities and Nucleophilicities of 1, 3, 5‐Tris(dialkylamino)benzenes. Issue 46 (26th October 2021) - Micheletti, Gabriele; Mayer, Robert J.; Cino, Silvia; Boga, Carla; Mazzanti, Andrea; Ofial, Armin R.; Mayr, Herbert
Abstract: Equilibrium constants for the formation of Wheland complexes from 1, 3, 5‐tris(dialkylamino)benzenes and benzhydrylium ions (Ar2 CH + ) have been determined photometrically in dichloromethane solution at 20 °C. The Lewis basicity of the ring carbons increases in the series trimorpholinobenzene<tripiperidinobenzene<tripyrrolidinobenzene. Wheland complexes, which are formed with equilibrium constants 10 2 < K /M −1 <10 6 in the reactions of triaminobenzenes with carbenium ions, show temperature‐dependent dynamic 1 H NMR spectra, due to rapid reverse reactions and recombination at different positions of the triaminobenzenes. Since the rates of the formation of the Wheland complexes are too high to be measured directly, they were calculated as the product of photometrically determined equilibrium constants and the rate constants for the reverse reactions, which were derived from the dynamic 1 H NMR spectra. The experimentally determined equilibrium and rate constants were in good agreement with the results of DFT calculations using the SMD solvent model. The calculations show that in all cases the Wheland complexes are thermodynamically more stable than the ammonium ions formed by attack of the benzhydrylium ions at the amino group of the title compounds, which explains the exclusive formation of Wheland complexes in thermodynamically controlled reactions. With nucleophilicity parameters in the range 10< N <15 the triaminobenzenes have comparable nucleophilic reactivities as enamines, silyl ketene acetals as well as stabilized phosphonium and sulfonium ylides. Abstract : Equilibrium constants for the formation of 3xy have been determined photometrically. The Lewis basicity of the ring carbons trend is: trimorpholinobenzene 1a 1b 1c ; nucleophilicity parameters are in the range 10< N <15. Some complexes show temperature‐dependent NMR spectra, due to rapid reverse reaction and recombination at different positions of the ring. DFT calculations agree with experimental data.